“We have nice policies but…”: implementation gaps in the Ghana adolescent health service policy and strategy (2016–2020) - Agblevor, Emelia Afi; Darko, Natasha Afua; Acquah, Priscilla Ama; Addom, Selasie; Mirzoev, Tolib; Agyepong, Irene Akua (Frontiers in Public Health, 2023)
Although policies for adolescent health exist in Ghana, their implementation is challenging. Availability of services for adolescent sexual and reproductive health and adolescent mental health remains less than desired, with adolescent mental health being particularly neglected despite being an important contributor to poor health outcomes. This paper presents an analysis of gaps in the implementation of the Ghana Adolescent Health Service Policy and Strategy (2016-2020), including how and why the context influenced the observed implementation gaps. Data for this paper is drawn from seventeen (17) in-depth interviews with purposefully identified key stakeholders in adolescent mental, sexual and reproductive health across the national and subnational levels; four (4) focus group discussions (FGDs) with district health management teams and eleven (11) FGDs with adolescents in and out of schools in four selected districts in the Greater Accra region. Data was analysed using both inductive and deductive approaches. The deductive analysis drew on Leichter’s conceptualization of context as structural, cultural, situational, and environmental. Of the 23 planned strategies and programs for implementing the policy, 13 (57%) were partially implemented, 6 (26%) were not implemented at all and only 4 (17%) were fully implemented. Multiple contextual factors constrained the policy implementation and contributed to the majority of strategies not being implemented or partially implemented. These factors included a lack of financial resources for implementation at all levels of the health system and the related high dependence on external funding for policy implementation. Service delivery for adolescent mental health, and adolescent sexual and reproductive health, appeared to be disconnected from the delivery of other health services, which resulted in weak or low cohesion with other interventions within the health system. Bottom-up approaches that engage closely with adolescent perspectives and consider structural and cultural contexts are essential for effective policy implementation. It is also important to apply systemic and multi-sectoral approaches that avoid fragmentation and synergistically integrate policy interventions.